A diurnal rhythm in brown adipose tissue causes rapid clearance and combustion of plasma lipids at wakening - Van Den Berg, R; Kooijman, S; Noordam, R; Ramkisoensing, A; Abreu-Vieira, G; Tambyrajah, L; Dijk, W; Ruppert, P; Mol, I; Kramar, B; Caputo, R; Puig, L; et al. (Elsevier, 2018)
Many favorable metabolic effects have been attributed to thermogenic activity of brown adipose tissue (BAT). Yet, time of day has rarely been considered in this field of research. Here, we show that a diurnal rhythm in BAT activity regulates plasma lipid metabolism. We observed a high-amplitude rhythm in fatty acid uptake by BAT that synchronized with the light/dark cycle. Highest uptake was found at the onset of the active period, which coincided with high lipoprotein lipase expression and low angiopoietin-like 4 expression by BAT. Diurnal rhythmicity in BAT activity determined the rate at which lipids were cleared from the circulation, thereby imposing the daily rhythm in plasma lipid concentrations. In mice as well as humans, postprandial lipid excursions were nearly absent at waking. We anticipate that diurnal BAT activity is an important factor to consider when studying the therapeutic potential of promoting BAT activity.